Neuromuscular fatigue according to injury history in the acceleration phase of a repeat sprint ability test: preliminary results - Armada-Cortés, E.; Benítez-Muñoz, J. A.; Sánchez-Sánchez, J.; San Juan, A. F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Sprinting is a fundamental component of the professional soccer player`s ability to achieve the highest performance in the sport (1) and the hamstrings muscles are crucial in sprint acceleration performance and maximal sprinting (2). The aim of this preliminary study was to analyze the influence of hamstring injury history on the neuromuscular fatigue in the acceleration phase produced by an RSA test in elite female football players.